Integrating BSF larvae for the sustainable bioconversion of banana peels and sprout hulls waste - Rizkawati, Vina; Andhini, Shabrina Lathiifah; Noer, Mohamad Isnin; Yudistira, Dwi Harya; Kurniati, Tri Handayani; Lisanti, Elsa; Komala, Ratna; Herlin, Weri (Universitas Muhammadiyah Surakarta, 2026)
The management of organic waste presents a significant challenge in Indonesia, especially fruit and vegetable by-products. Black Soldier Fly (BSF, Hermetia illucens) larvae offer an effective solution due to their high potential for organic waste conversion. This study investigated the efficacy of BSF larvae in reducing and bioconverting organic waste composed of banana peels and sprout hulls, and examined the influence of EM4 fermentation on larval growth performance. Waste Reduction Index (WRI) and bioconversion rate (BCR) were calculated as percentages and analyzed descriptively, followed by the Kruskal–Wallis test. Furthermore, larval length and body weight were measured at 7, 11, 14, and 18 days of larval age and analyzed using Kruskal–Wallis with Dunn’s post-hoc test. The results showed that EM4–fermented substrates containing a 1:3 ratio of banana peels to sprout hulls showed the highest waste reduction and bioconversion potential among all mixture treatments (P < 0.05). Although larval length and weight were lower than control substrate, no significant difference in larval length was detected, while individual larval weight was significantly higher compared to other organic waste combinations (P < 0.001). In this study, EM4 fermentation enhanced lignocellulosic degradation, improving substrate digestibility for BSF larvae and optimizing bioconversion efficiency, thus supporting more sustainable organic waste management strategies.